The influence of social media marketing and brand trust to purchase intention - Dhea Fitriani Nur Hamidah; Terra Saptina Maulani (Marketing Management Studies, 2023)
JD.ID is an e-commerce engaged in online shopping services but from year to year JD.ID has experienced a long-term decline in website visitors, the number of instagram followers is not comparable to competitors, and JD.ID is not included in the 2022 Top Brand Index This shows that social media marketing, brand trust, and purchase intention in JD.ID still have many shortcomings. This research aims at influence of social media marketing and brand trust to purchase intention on e-commerce jd.id. The methodology used is descriptive method and verifikatif with data collection through the distribution of the questionnaire to 100 respondents who follow instagram and ever shopped in e-commerce JD.ID. Analysis of the validity of the data used, reliability test, the classical assumption, multiple linear regression analysis, a correlation coefficient analysis and determination, the research and hypotheses (partial t-test and simultaneous f-test). A program used to analyse data using statistical package for social sciences (SPSS) for windows. Based on the research done obtained the regression equation is = 5,152 + 0,250 X1 + 0,569 X2. This study found the influence of social media marketing and brand trust on purchase intention of 85.8% and the rest is influenced by other factors not examined in this study. The research results show that social media marketing and brand trust have had a positive impact and significant impact on consumer interest in buying.Data analysis revealed that brand trust have more impact than social media marketing to interest the purchase. Hence, social media marketing and brand trust played an important role in e-commerce interest in buying by directly influence.